Laços rompidos, perdas ressignificadas: uma análise dos afetos na prosa poética e no poesia em prosa de José Luís Peixoto - Schuler, Letícia Simões Velloso (2023)
This dissertation seeks to understand affections and their possibilities for resignification in the prose and poetry of José Luís Peixoto based on the dialogical relationships between literature, psychoanalysis and philosophy. Our literary focus focuses on the analysis of Morreste-me (2000), a novel that marks the author's debut on the literary scene, and A Criança em ruinas (2001), in terms of family, affection, loss, suffering. To this end, we present the understanding of some philosophers in order to demarcate the change that accompanied the understanding of affect to philosophy, from the understanding of pathos to Antiquity. Next, we embark on a discussion of the theory about affect seen from a psychoanalytic perspective, based on the writings of Freud and Lacan, as well as their commentators. Therefore, to understand the new ways of creating poetry and prose, in an attempt to understand the degree of subjectivity that can be achieved, we look at the literary genres of poetic prose and prose poem. In order to illustrate the poetics centered on affections in the corpora, we establish approximations between a literature that distances itself from delimitations and opens space for questioning the form, for different forms of language use, becoming fertile ground for the perception of subjectivities and affections that overlap with it.